Medication Overuse Headache: History, Features, Prevention and Management Strategies - Saper, Joel R.; Da Silva, Arnaldo Neves (CNS drugs, 2013)
Medication overuse headache (MOH) is a daily, or almost daily, headache form that arises from overuse of one or more classes of migraine-abortive or analgesic medication. The main classes of drugs that cause MOH are opioids, butalbital-containing mixed analgesics, triptans, ergotamine tartrate derivatives, simple analgesics (except for plain aspirin), and perhaps non-steroidal anti-inflammatory drugs. MOH can be debilitating and results from biochemical and functional brain changes induced by certain medications taken too frequently. At this time, migraine and other primary headache disorders in which migraine or migraine-like elements occur seem exclusively vulnerable to the development of MOH. Other primary headache disorders are not currently believed to be vulnerable. The treatment of MOH consists of discontinuation of the offending drug(s), acute treatment of the withdrawal symptoms and escalating pain, establishing a preventive treatment when necessary, and the implementation of educational and behavioral programs to prevent recidivism. In most patients, MOH can be treated in the outpatient setting but, for the most difficult cases, including those with opioid or butalbital overuse, or in patients with serious medical or behavioral disturbances, effective treatment requires a multidisciplinary, comprehensive headache program, either day-hospital with infusion or an inpatient hospital setting.